Voice over Internet Protocol over Wireless Local Area Network: A Review - Ayodele Hephibah; Oluwafemi Ilesanmi Banjo; Moses Oluwamuyiwa Olla (Journal La Multiapp, 2022)
The use of Voice over Wireless Local Area Network is seeing a meteoric rise in popularity as a result of its simplicity, non-intrusiveness, and cheap cost of implementation, as well as its low cost of maintenance, universal coverage, and fundamental roaming capabilities. Nevertheless, deploying Voice over Internet Protocol (VoIP) over Wireless Local Area Network (WLAN) is a challenging task for many network managers, architects, planners, designers, and engineers. Because of this, there is a need for a guideline to design, model, and simulate the network before it is deployed. In this work, a variety of models, including mathematical, theoretical, statistical, and graphical models, that are used to measure the quality and features of VoIP are discussed.